Implementasi Manajemen Pembiayaan Dalam Meningkatkan Mutu Pendidikan di RA Mambaul Ulum Sumurgung Montong Tuban - Siti Fatimahh (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2020)
This research aimed to describe the financing management planning, implementation of education financing management and education financing control to improve the quality of education in RA Mambaul Ulum Sumurgung Montong Tuban. The method used in this research through observation, interviews and documentation. The results showed that 1) financing management planning was arried out by referring to the budget ceiling, not exceeding the budget determined by the government or financing from parents or the community, if the source of cost comes from the government then must look at the rules that have been determined by the government, if financing income comes from the community, so the financing management plan was carried out according to the principle of primary school needs to tertiary needs but within limits did not violate the rules 2) Madrasah financing implementation activities included two major activities, consisting of school financial revenues and expenditures. The financing management activities included bookkeeping or financial management activities 3) control/evaluation included the activities of checking and evaluating the plan and implementation of education funding can be carried out in accordance with the initial financing plan and its implementation.